2019
DOI: 10.1111/cts.12705
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of the Mineralocorticoid Receptor Modulator AZD9977 in Healthy Men: A Phase I Multiple Ascending Dose Study

Abstract: Excessive activation of the mineralocorticoid receptor (MR) underlies the pathophysiology of heart failure and chronic kidney disease. Hyperkalemia risk limits the therapeutic use of conventional MR antagonists. AZD9977 is a nonsteroidal, selective MR modulator that may protect nonepithelial tissues without disturbing electrolyte balance. This phase I study investigated the safety, tolerability, pharmacokinetics, and pharmacodynamics of multiple oral doses of AZD9977 in healthy volunteers. Twenty‐seven male pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…This study suggested that aldosterone‐induced decrease in Na + /K + ratio is not affected by AZD9977. In a dose‐escalation study, AZD9977 did not alter the serum Na + /K + ratio in healthy volunteers (Whittaker et al, 2020). AZD9977 has different interaction patterns with MR, with differential cofactor recruitment, which is considered responsible for the renoprotective effect devoid of hyperkalemia (Bamberg et al, 2018).…”
Section: Hyperkalemia With Mr Antagonistmentioning
confidence: 99%
“…This study suggested that aldosterone‐induced decrease in Na + /K + ratio is not affected by AZD9977. In a dose‐escalation study, AZD9977 did not alter the serum Na + /K + ratio in healthy volunteers (Whittaker et al, 2020). AZD9977 has different interaction patterns with MR, with differential cofactor recruitment, which is considered responsible for the renoprotective effect devoid of hyperkalemia (Bamberg et al, 2018).…”
Section: Hyperkalemia With Mr Antagonistmentioning
confidence: 99%
“…Eplerenone, a second-generation MR blocker, had improved specificity for the MR, thus reducing the frequency of serious sex hormone-related adverse events [14][15][16]. More recently, the highly selective nonsteroidal MR blockers esaxerenone, finerenone, apararenone, and AZD9977 have been successively developed [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacodynamic and pharmacokinetic characteristics of non‐steroidal mineralocorticoid receptor antagonists and spironolactone. 1 Arai, Homma, et al (2015); 2 Yamada et al (2019); 3 Ito et al (2019); 4 Ito, Itoh, et al (2020); 5 Ito, Kashihara, et al (2020); 6 Bamberg et al (2018); 7 Whittaker et al (2020); 8 Nakamura and Kawaguchi (2021); 9 Wada et al (2021); 10 Bakris, Yang, and Pitt (2020); 11 Bakris et al (2021); 12 Pitt et al (2012); 13 Amazit et al (2015); 14 Grune et al (2018); 15 Heinig et al (2016); 16 Gerisch et al (2018); 17 Bakris et al (2015); 18 Bakris, Agarwal, et al (2020); 19 Pitt et al (2013); 20 Pitt et al (2021); 21 Gardiner et al (1989); 22 Karim et al (1976); 23 Karim (1978); 24 Agarwal et al (2019); 25 Weinberger et al (2002); 26 Williams et al (2015); 27 Bianchi et al (2006). 7α‐TMS, 7α‐thiomethylspirono‐lactone; CKD, chronic kidney disease; comp., comparison; DKD, diabetic kidney disease; HT, arterial hypertension; modest, ≤5‐mmHg SBP change; nsMRA, non‐steroidal MRA; rHT, uncontrolled/resistant hypertension; rHT‐CKD, uncontrolled/resistant hypertension and chronic kidney disease; robust, ≥10‐mmHg SBP change; SBP, systolic BP; sMRA, steroidal mineralocorticoid receptor antagonist; wCHF, worsening of chronic heart failure…”
Section: Novel Non‐steroidal Mrasmentioning
confidence: 99%
“…In clinical Phase I studies, AZD9977 was safe and well tolerated with a plasma half‐life after single dosing of 2–3 h and after 8‐day administration between 4 and 9 h (Erlandsson et al, 2018; Whittaker et al, 2020) (Figure 3); 24–37% of AZD9977 was excreted in the urine (Whittaker et al, 2020) (Figure 3). After a fludrocortisone challenge, a single dose of AZD9977 (200 mg) resulted in a significant increase of the urine Na + /K + ratio similarly to eplerenone (100 mg) (Erlandsson et al, 2018).…”
Section: Novel Non‐steroidal Mrasmentioning
confidence: 99%